Differential Diagnosis of Acute Stroke and Viral Encephalitis - I.V. Bogadelnikov; L.I. Prokudina; Ye.V. Zdyrko; T.N. Bezdolnaya (Zaslavsky O.Yu., 2012)
At the present time, there has been an increase in the frequency of ischemic and hemorrhagic stroke in children. The clinical picture of the disease has similar features to the one of viral encephalitis. Differential diagnosis is necessary to choose correct treatment tactics.